2017
DOI: 10.1111/tmi.12869
|View full text |Cite
|
Sign up to set email alerts
|

Mouthing of Soil Contaminated Objects is Associated with Environmental Enteropathy in Young Children

Abstract: Abstractobjective To characterise childhood mouthing behaviours and to investigate the association between object-to-mouth and food-to-mouth contacts, diarrhoea prevalence and environmental enteropathy.methods A prospective cohort study was conducted of 216 children ≤30 months of age in rural Bangladesh. Mouthing contacts with soil and food and objects with visible soil were assessed by 5-h structured observation. Stool was analysed for four faecal markers of intestinal inflammation: alpha-1-antitrypsin, myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 60 publications
(93 reference statements)
6
40
1
Order By: Relevance
“…We found the highest prevalence of caregiver‐reported direct soil ingestion among children aged 12–24 months, which is consistent with two previous structured observation studies in Bangladesh – one observing the number of times children put soil in their mouths and one observing the number of times children put soil in their mouth or had any soil contact . However, our study found that caregiver‐reported direct soil ingestion was observed in 19% of children aged 24–36 months, illustrating that it may be important to include children in this age group in future soil ingestion studies, even if these children may have lower frequencies of hand‐to‐mouth or object‐to‐mouth contact.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found the highest prevalence of caregiver‐reported direct soil ingestion among children aged 12–24 months, which is consistent with two previous structured observation studies in Bangladesh – one observing the number of times children put soil in their mouths and one observing the number of times children put soil in their mouth or had any soil contact . However, our study found that caregiver‐reported direct soil ingestion was observed in 19% of children aged 24–36 months, illustrating that it may be important to include children in this age group in future soil ingestion studies, even if these children may have lower frequencies of hand‐to‐mouth or object‐to‐mouth contact.…”
Section: Discussionsupporting
confidence: 89%
“…For these children, we assumed the activity reported by caregivers as soil ingestion was indirect soil ingestion through hand‐to‐mouth contact and not intentional direct soil ingestion, and we have not classified these children as participating in soil ingestion in our analyses. Due to high levels of hand‐to‐mouth contact reported for young children in observation studies , it is likely this type of indirect soil ingestion through hand‐to‐mouth contact would be occurring in many of the children included in our analysis even when it has not been reported as soil ingestion by caregivers, and therefore our analysis excludes this activity and focuses on intentional soil ingestion where a child has directly picked up and put soil particles into his/her mouth. Three children with caregivers that responded ‘don't know’ when asked if they had observed their child ingesting soil were excluded from our analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent work has found significant associations between poor household hygiene practices and elevated faecal markers of EE and impaired growth among young children [6,7,19,28,29]. In our cohort study in rural Bangladesh, we found that animals in the child's sleeping space and poor caregiver hand hygiene were associated with elevated faecal markers of EE [7].…”
Section: Introductionmentioning
confidence: 47%
“…Previous work from our cohort study found poor child and caregiver hygiene practices were significantly associated with elevated EE markers and impaired growth among young children . This study has built on this previous work by investigating the influence of enteric infections on faecal markers of EE and impaired growth.…”
Section: Discussionmentioning
confidence: 93%